Wise Gals : The Spies Who Built the CIA and Changed the Future of Espionage - Holt, Nathalia (New York G. P. Putnam's Sons, 2022)
"From the New York Times bestselling author of Rise of the Rocket Girls comes the never-before-told story of a small cadre of influential female spies in the precarious early days of the CIA--women who helped create the template for cutting-edge espionage (and blazed new paths for equality in the workplace) in the treacherous post-WWII era."-- Provided by publisher
Include Illustrations and Index
Keywords: Spies -- Women intelligence officers -- United States. Central Intelligence Agency -- Intelligence service